Oriented Crystallization of Mixed‐Cation Tin Halides for Highly Efficient and Stable Lead‐Free Perovskite Solar Cells. (4th May 2020) - Yu, Bin‐Bin; Liao, Min; Zhu, Yudong; Zhang, Xusheng; Du, Zheng; Jin, Zhixin; Liu, Di; Wang, Yiyu; Gatti, Teresa; Ageev, Oleg; He, Zhubing
Abstract: As the most promising lead‐free branch, tin halide perovskites suffer from the severe oxidation from Sn 2+ to Sn 4+, which results in the unsatisfactory conversion efficiency far from what they deserve. In this work, by facile incorporation of methylammonium bromide in composition engineering, formamidinium and methylammonium mixed cations tin halide perovskite films with ultrahighly oriented crystallization are synthesized with the preferential facet of (001), and that oxidation is suppressed with obviously declined trap density. MA + ions are responsible for that impressive orientation while Br ‐ ions account for their bandgap modulation. Depending on high quality of the optimal MA0.25 FA0.75 SnI2.75 Br0.25 perovskite films, their device conversion efficiency surges to 9.31% in contrast to 5.02% of the control formamidinium tin triiodide perovskite (FASnI3 ) device, along with almost eliminated hysteresis. That also results in the outstanding device stability, maintaining above 80% of the initial efficiency after 300 h of light soaking while the control FASnI3 device fails within 120 h. This paper definitely paves a facile and effective way to develop high‐efficiency tin halide perovskites solar cells, optoelectronic devices, and beyond. Abstract : MABr induces the remarkably oriented growth of tin halide perovskite films (MA x FA1− x SnI3− x Br x ) by alloying, which results in an optimal device conversion efficiency of 9.31% enhanced from 5.02% of the pristine FASnI3 device and maintained above 80% of the initial efficiency after 300 h light soaking while the control device fails within 120 h.